Utility of 2D Video Analysis for Assessing Frontal Plane Trunk and Pelvis Motion during Stepping, Landing, and Change in Direction Tasks: A Validity Study - Rachel K Straub; Christopher M Powers (North American Sports Medicine Institute, 2022)
# Background Excessive frontal plane motion of the trunk and/or pelvis has been implicated in numerous clinical conditions. To date, it is unclear whether 2D video is an appropriate surrogate for assessing frontal plane trunk and pelvis motion as a comprehensive validity study across a wide range of movements using a consistent methodology has not been performed. # Hypothesis/Purpose The purpose of the current study was to assess the concurrent validity and agreement of frontal plane pelvis and trunk motion obtained with 2D video against the respective 3D angles during stepping, landing, and change in direction tasks. # Design Crossover Study Design. # Methods 3D kinematics and 2D frontal plane video were obtained from 39 healthy participants (15 males and 24 females) during five athletic tasks (step down, lateral shuffle, deceleration, triple hop, side-step-cut). Data were extracted at peak knee flexion. Pearson's correlation analysis was used to assess the association between the 2D and 3D frontal plane angles at the trunk and pelvis. Bland Altman plots were used to assess the level of agreement between the 2D and 3D frontal plane angles at the trunk and pelvis. # Results 2D and 3D frontal plane angles for all tasks were correlated in a positive direction at the pelvis (r = 0.54 to 0.73, all p \< 0.001) and trunk (r = 0.81 to 0.92, all p \< 0.001). Absolute agreement in the frontal plane for all tasks and angles was below 5°. However, the 95% limits of agreement across tasks ranged from -12.8° to 21.3° for the pelvis and -11.8° to 9.4° for the trunk. # Conclusions The use of 2D video to assess frontal plane trunk and pelvis motion is appropriate during stepping, landing, and change of direction tasks, however caution is advised when high levels of agreement or accuracy is required.